Flagship Class Management: The Secret Behind Student Achievement - Latifah, Mar’atul; Jinan, Mutohharun (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study explores the strategies behind managing superior classes to enhance student academic performance, including supporting and inhibiting factors, as well as solutions to overcome challenges. Using a qualitative research model, data were collected through participant observations (both formal and informal) and in-depth interviews. The findings reveal several key strategies employed by MTs N 1 Klaten to manage superior classes effectively. These include creating an optimal classroom atmosphere, addressing disruptive behaviors, fostering discipline, and building harmonious relationships between teachers and students. Supporting factors for these strategies include the curriculum, teachers, students, classroom facilities, and class dynamics. Conversely, challenges arise from teacher limitations, student behavior, family environments, and inadequate facilities. Solutions implemented include selecting highly qualified teachers tailored to the superior class programs (e.g., IT and science teachers), conducting a strict student selection process to manage demand, and holding regular meetings with parents. Additional facilities such as science and IT laboratories further support enhanced learning experiences, ensuring the successful implementation of superior class programs.